Hybridation of Labeling Schemes for Efficient Dynamic Updates - Su Cheng Haw; Samini Subramaniam; Wei Siang Lim; Fang Fang Chua (Institute of Advanced Engineering and Science, 2016)
With XML as the leading standard for data representation over the Web, it is crucial to store and query XML data. However, relational databases are the dominant database technology in most organizations. Thus, replacing relational database with a pure XML database is not a wise choice. One most prominent solution is to map XML into relational database. This paper introduces a robust labeling scheme which is a hybrid labeling scheme combining the beauty features of extended range and ORDPATH schemes to supports dynamic updates. In addition, we also proposed a mapping scheme based on the hybrid labeling scheme. Our proposed approach is evaluated in terms of (i) loading time, (ii) storage size, (iii) query retrieval time, and (iv) dynamic updates time, as compared to ORDPATH and ME schemes. The experimental evaluation results shows that our proposed approach is scalable to support huge datasets and dynamic updates.